Production of methyl caffeate as an intermediate product to produce caffeic acid phenethyl ester by esterification using cation-exchange resin - Rani Salsabila; Meka Saima Perdani; Naomi Shibasaki Kitakawa; Heri Hermansyah (Energy Reports, 2020)
Caffeic acid (CA) could be considered as an important natural anti-oxidant. However, the low solubility and stability of CA in various solvent is limiting the application in industry. It is advantageous to synthesize alkyl ester of caffeic acid based on both their biological function and potential application. One of the caffeic acid derivatives called caffeic acid phenethyl ester (CAPE) is a compound with numerous important biological activities. To synthesize CAPE one of the method used is catalyzed esterification of caffeic acid and phenethyl alcohol using ion exchange resin catalyst. The first step of the process is to perform esterification of caffeic acid and methanol to produce methyl caffeate (MC). MC would then be used to produce CAPE in the presence of phenethyl alcohol. Herein, the reaction condition and kinetic parameters for the synthesis of MC using cation-exchange resin as a catalyst were investigated, and the product was confirmed by high-performance liquid chromatography (HPLC). The highest yield of MC catalyzed by cation-exchange resin attained under the optimum condition as follows: reaction temperature of 60~°C and a reaction time of 4 h. The esterification kinetics of CA and methanol is described by the pseudo-homogeneous first order model. The relationship between temperature and the forward rate constant gives activation energy of 51 kJ/mol. These results indicated that cation-exchange resin possesses high catalytic activity in the synthesis of MC, which is an efficient catalyst suitable for MC production.
Keywords: 330; Caffeic acid; Cation exchange; Methyl caffeate